Sri Lanka : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Sri Lanka. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2022)
COVID-19 severely hit the economy, causing a loss of tourism receipts and necessitating several strict lockdowns. Pre-pandemic tax cuts and the impact of COVID-19 led to fiscal deficits larger than 10 percent of GDP in 2020 and 2021 and a rapid increase in public debt to 119 percent of GDP in 2021. Sri Lanka's access to international capital markets was lost in 2020, prompting a decline of international reserves to critically low levels and large-scale direct lending to the government by the Central Bank of Sri Lanka (CBSL). External debt repayments and a widening current account deficit have led to foreign exchange (FX) shortages, while the official exchange rate has been de facto fixed since April 2021. Inflation is on the rise, reaching double digits in December 2021, reflecting imported inflation, supply shocks, and a pickup in domestic demand amid loose monetary policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Sri Lanka